If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(6t + -3) + 4r = 0 Reorder the terms: 8(-3 + 6t) + 4r = 0 (-3 * 8 + 6t * 8) + 4r = 0 (-24 + 48t) + 4r = 0 Reorder the terms: -24 + 4r + 48t = 0 Solving -24 + 4r + 48t = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 4r + 24 + 48t = 0 + 24 Reorder the terms: -24 + 24 + 4r + 48t = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 4r + 48t = 0 + 24 4r + 48t = 0 + 24 Combine like terms: 0 + 24 = 24 4r + 48t = 24 Add '-48t' to each side of the equation. 4r + 48t + -48t = 24 + -48t Combine like terms: 48t + -48t = 0 4r + 0 = 24 + -48t 4r = 24 + -48t Divide each side by '4'. r = 6 + -12t Simplifying r = 6 + -12t
| 1/7-1/3v=-1/2 | | 5.9m+8.33=-2.88 | | x-y+12x+y=3 | | x-85.13=11.06 | | 3.96=18s | | m=-4(7,-6) | | m=-4(7-6) | | (Y+6)(3y-3)=0 | | 7m-3=-22.96+9 | | 8.56*7= | | y=2(3x-4) | | x+2-5=0 | | 2+6x-1+4x= | | 9x=12x-30 | | y-x+4y=3x | | (6y+7)-(5+5y)=11 | | 2j=18-28 | | (2x-7)(x+4)=42 | | 3c-c-2=8 | | (160)^3/5 | | Y+(9-8y)= | | 9/4x-x=80 | | 75=-5(-3-4-3) | | 2x^2+3x-2=5 | | 75=-5(-3-4-4) | | 9/x=4/10 | | x(1.26-.00042x)=0 | | 1.26x-.00042x^2=0 | | 75=-5(-3-4+3) | | d^3y/dx^3=sin(7x) | | x+.22x=115 | | 3x+2y=5x+4y |